Curcumin in vitro Neuroprotective Effects Are Mediated by p62/keap-1/Nrf2 and PI3K/AKT Signaling Pathway and Autophagy Inhibition - Li, Xin; Sung, Peng; Zhang, Dongme; Yan, Limin (Physiological research, 2023)
Oxidative stress and autophagy are potential mechanisms associated with cerebral ischemia/reperfusion injury (IRI) and is usually linked to inflammatory responses and apoptosis. Curcumin has recently been demonstrated to exhibit anti-inflammatory, anti-oxidant, anti-apoptotic and autophagy regulation properties. However, mechanism of curcumin on IRI-induced oxidative stress and autophagy remains not well understood. We evaluated the protective effects and potential mechanisms of curcumin on cerebral microvascular endothelial cells (bEnd.3) and neuronal cells (HT22) against oxygen glucose deprivation/reoxygenation (OGD/R) in vitro models that mimic in vivo cerebral IRI. The cell counting kit-8 (CCK-8) and lactate dehydrogenase (LDH) activity assays revealed that curcumin attenuated the OGD/R-induced injury in a dose-specific manner. OGD/R induced elevated levels of inflammatory cytokines TNF-alpha, IL-6 as well as IL-1beta, and these effects were notably reduced by curcumin. OGD/R-mediated apoptosis was suppressed by curcumin via upregulating B-cell lymphoma-2 (Bcl-2) and downregulating Bcl-associated X (Bax), cleaved-caspase3 and TUNEL apoptosis marker. Additionally, curcumin increased superoxide dismutase (SOD) and glutathione (GSH), but suppressed malondialdehyde (MDA) and reactive oxygen species (ROS) content. Curcumin inhibited the levels of autophagic biomarkers such as LC3 II/LC3 I and Beclin1. Particularly, curcumin induced p62 accumulation and its interactions with keap1 and promoted NF-E2-related factor 2 (Nrf2) translocation to nucleus, accompanied by increased NADPH quinone dehydrogenase (Nqo1) and heme oxygenase 1 (HO-1). Treatment of curcumin increased phosphorylation-phosphatidylinositol 3 kinase (p-PI3K) and p-protein kinase B (p-AKT). The autophagy inhibitor 3-methyladenine (3-MA) activated the keap-1/Nrf2 and PI3K/AKT pathways. This study highlights the neuroprotective effects of curcumin on cerebral IRI.
Keywords: Antioxidants; Proto-Oncogene Proteins c-akt; NF-E2-Related Factor 2; Autophagy; oxidační stres; Phosphatidylinositol 3-Kinases; Curcumin; kurkumin; Oxidative Stress; fosfatidylinositol-3-kinasy; faktor 2 související s NF-E2; signální transdukce; Endothelial Cells; Signal Transduction; protoonkogenní proteiny c-akt; autofagie; Neuroprotective Agents; KEAP-1; Oxygen; antioxidancia; endoteliální buňky; Kelch-Like ECH-Associated Protein 1; kyslík; neuroprotektivní látky